Exam Help
Exam Help
Exam Help
y = mx + c
Now from the graph,
When x= 0, y= 6. Use these values in the above equation:
6 = m*0 + c
i.e. 6 = c.
Now you have the value of c for your straight line which you will use here onwards.
From the graph, we see that when y= 0, x= 2. Use these values in the equation:
0 = m*2 + 6
i.e. -6 = m*2
i.e. -3 = m
Now you have values for both c and m which makes equation of the line to be
y= -3x + 6 .. (This is equation of line in the graph)
Now to find the inverse of this function, place x in place of y and y in place of x and solve for y.
x = -3y + 6
i.e. x 6 = -3y
i.e. y =
i.e. y = -